Disseminated cutaneous histoplasmosis, an initial manifestation of hiv, diagnosed with fine needle aspiration cytology - Sankha Koley; Rajesh Kumar Mandal; Kalyan Khan; Sanjiv Choudhary; Sabyasachi Banerjee (Wolters Kluwer Medknow Publications, 2014)
Acute progressive disseminated histoplasmosis (PDH) may be the initial manifestation of human immunodeficiency virus (HIV). However, cutaneous involvement is very rare. We present an unusual case of acute PDH with multiple diffuse cutaneous papulonodular lesions predominantly on the face, trunk, and upper extremities, diagnosed initially with fine needle aspiration cytology (FNAC). Subsequent serological tests revealed positivity for antibodies for HIV 1 and 2. The cytomorphological features were further confirmed by biopsy and histochemical stains. FNAC is a rapid, cost-effective tool that may be utilized in the diagnosis of papulonodular forms of PDH and for initiating prompt therapy. We discuss the clinical features, clinical differentials, and treatment of the condition.